When Fear of Covid Is Not the Main Reason to Use Online Technology - Kusuma, I Gusti Agung Eka Teja; Yuliadewi, Nyoman Wiwiek; Atmaja, Ni Putu Cempaka Dharmadewi (The Asian Journal of Technology Management (AJTM), 2024)
Abstract. Purpose: analyzing how fear of Covid-19 influences technology utilization attitude towards intention to use. Design/methodology/approach: This study used a quantitative approach conducted post Covid-19. Involving a sample of 138 mobile application users for health insurance services in Bali, Indonesia, by utilizing the PLS-SEM model analysis tool. Findings: Technology Acceptance Model (TAM), through its two elements, Perceived usefulness (PU) and Perceived ease of use (PEOU), has proven to significantly form a supportive attitude about the use of information technology in the Covid-19 pandemic, as well as the influence of attitudes towards behavior intention to use (BIU) in the use of technology has also been proven clearly in the context of TAM. But TAM's ability to form intention directly can only be confirmed through PU, while PEOU has not been able to be proven. Fear of Covid-19 has not been shown to play a role in moderating the influence of attitude on intention. Practical/implications: Encouraging attitude is very important to use technology based on usability and ease of using technology. However, it is not feasible to consider fear of Covid-19 as a factor to encourage people's attitudes towards technology to promote intention to use application technology for transactions. Originality/value: This study provides new insights, first to collaborate on fear of Covid on TAM and TRA. Examining the impact of Covid-19 fear moderation on the acceptance of mobile applications in the health insurance service industry and providing important information that people's behavior does not consider the dangers of Covid-19 when adopting information technology services in the future. Keywords: Technology acceptance model, perceived usefulness, perceive ease of use, attitude toward using, fear of Covid-19